Water circulation pattern of Kuala Terengganu - Marghany, Maged Mahmoud (Fakulti Pengajian Maritim dan Sains Marin, 2011)
The aim of this study was to determine the type of the current patterns in the coastal water of Kuala Terengganu. This study was divided in two parts. The first one was to determine the pattern of thermohaline circulation. This was done by sampling of. 25 stations along the coastal water of Kuala Terengganu. The second one was to measure the subsurface current by ONO-self recording current meter and drogue. The current meter was deployed at Station 1 while the drogue was deployed at Stations 3 and 5.